A Composite Structure for Fast Name Prefix Lookup - Hu, Jiawei; Li, Hui (Frontiers in ICT, 2019)
Name-based forwarding plane is a critical but challenging component for Named Data Networking (NDN), where the hash table is an appealing candidate for data structure utilized in FIB on the benefit of its fast lookup speed. However, the hash table is flawed that it does not naturally support the longest-prefix-matching (LPM) algorithm for name-based forwarding. To support LPM in the hash table, besides the linear lookup, the random search (such as binary search) aims at increasing the lookup speed by reconstructing the FIB and optimizing the search path. We propose a composite data structure for random search based on the combination of hash table and trie; the latter is introduced preserve the logical associations among names, so as to recycle memory and prevent the so-called backtracking problem, thus enhancing the lookup efficiency. The experiment indicates the superiority of our scheme in lookup speed, the impact on memory consumption has also been evaluated.